MassCascade: Visual Programming for LC‐MS Data Processing in Metabolomics. Issue 4 (22nd April 2014) - Beisken, Stephan; Earll, Mark; Portwood, David; Seymour, Mark; Steinbeck, Christoph
Abstract Liquid chromatography coupled to mass spectrometry (LC‐MS) is commonly applied to investigate the small molecule complement of organisms. Several software tools are typically joined in custom pipelines to semi‐automatically process and analyse the resulting data. General workflow environments like the Konstanz Information Miner (KNIME) offer the potential of an all‐in‐one solution to process LC‐MS data by allowing easy integration of different tools and scripts. We describe MassCascade and its workflow plug‐in for processing LC‐MS data. The Java library integrates frequently used algorithms in a modular fashion, thus enabling it to serve as back‐end for graphical front‐ends. The functions available in MassCascade have been encapsulated in a plug‐in for the workflow environment KNIME, allowing combined use with e.g. statistical workflow nodes from other providers and making the tool intuitive to use without knowledge of programming. The design of the software guarantees a high level of modularity where processing functions can be quickly replaced or concatenated. MassCascade is an open‐source library for LC‐MS data processing in metabolomics. It embraces the concept of visual programming through its KNIME plug‐in, simplifying the process of building complex workflows. The library was validated using open data.